Nilai-Nilai Islam dalam Upacara Adat Pernikahan Sunda - Ilfa Harfiatul Haq (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2019)
Marriage is a bond that combines two people namelyem and women on the basic of love and of course with his permission. Marriage is realized with hope only once in a lifetime, so it is considered a sacred ritual. The author is interested in doing research with the theme of traditional marriage that is cultured with its religious side. The purpose of this study is to uncover the essence of the problem, namely Islamic values contained in the Sundanese wedding ceremony. This research was conducted using methods and approaches to Islamic studies. Marriage is carried out Islam with a blend of local culture, especially in the Sunda region. Sundanese custom marriages are held with several events which become traditions and characteristics of Sundanese culture, but contain Islamic values in it because they have gone through the process of Islamization. Islamic values that do not conflict with Shari'at Islam.